1994
DOI: 10.1007/bf02351875
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural changes during in vitro encystment ofBlastocystis hominis

Abstract: The morphological changes occurring in Blastocystis hominis at different time points following in vitro encystment were studied by electron microscopy. The following stages of the parasite were sequentially seen: (a) the amoebic form, which was irregular in shape, with a majority of the organelles being concentrated at the condensed cytoplasmic region; (b) the pre-cystic form, which was rounded and had an electron-dense material forming a homogeneous wall around the central body; and (c) the cystic form, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
34
0
3

Year Published

1994
1994
2013
2013

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 22 publications
9
34
0
3
Order By: Relevance
“…Experimental infectivity studies of BALB/c mice, Wistar rats, and a variety of bird species with the cyst form indicate that this form is undoubtedly the transmissible form of the parasite. The formation of in vitro-derived cysts by the incubation of vacuolar forms in encystation medium was reported previously (240,241,244,282). These "cysts" appear to be curiously similar to the classical granular forms, and the granules within the central vacuole were reported to be reproductive in nature (240,241,243).…”
Section: Morphological Formssupporting
confidence: 52%
See 1 more Smart Citation
“…Experimental infectivity studies of BALB/c mice, Wistar rats, and a variety of bird species with the cyst form indicate that this form is undoubtedly the transmissible form of the parasite. The formation of in vitro-derived cysts by the incubation of vacuolar forms in encystation medium was reported previously (240,241,244,282). These "cysts" appear to be curiously similar to the classical granular forms, and the granules within the central vacuole were reported to be reproductive in nature (240,241,243).…”
Section: Morphological Formssupporting
confidence: 52%
“…The formation of in vitro-derived cysts by the incubation of vacuolar forms in encystation medium was reported previously (240,241,244,282). These "cysts" appear to be curiously similar to the classical granular forms, and the granules within the central vacuole were reported to be reproductive in nature (240,241,243). It is likely that these are artifacts of culture induced by the encystation medium, as they bear no morphological similarity to the fecal cyst.…”
Section: Morphological Formsmentioning
confidence: 67%
“…The amoeboid form of B. hominis has been reported infrequently, and its morphological descriptions have yielded conflicting and confusing reports particularly on the presence of cell membrane, surface coat, central vacuole, and organelles (Zierdt 1973(Zierdt , 1991Zierdt and Tan 1976;McClure et al 1980;Dunn et al 1989;Suresh et al 1994b;Tan et al 2001). In the present study, two types of amoeboid forms were found, one contained a large central vacuole completely filled up with tiny electron-dense granules, and the other did not have a large central vacuole, but instead showed multiple small vacuoles in the cytoplasm.…”
Section: Discussionmentioning
confidence: 95%
“…A number of con¯icting de®nitions have been presented in the literature . Several studies suggest that this form extends pseudopodia and feeds on bacteria (Zierdt, 1973;Dunn et al, 1989;Suresh et al, 1994;Singh et al, 1995). A central vacuole was not noted, and the cells varied in diameter (approximately 3±8 mm).…”
Section: Amoeboid Formmentioning
confidence: 94%